Mechanical Properties of Concrete Block Containing Recycled Paper Sludge (RPS) as Replacement Material - tengku yusoff, tengku muhamad akmal; Bin Ahmad Jeni, Mohamad Luthfi; Bin Kosnin, Hilmi (Progress in Engineering Application and Technology, 2023)
The use of waste and recycled materials in construction and block production is one of the current investments made by all construction industries and the issue related to the waste paper is paper pollution. The main objective of this study is to investigate mechanical properties of recycle paper sludge as replacement material of sand in the concrete block and it can be proof by the data and result obtained from density test, water absorption test, sound absorption coefficient and thermal conductivity test. The main material are cement, sand, water and paper sludge as replacement material. The percentage of RPS used in this study consist 5%,10% and 15% and the optimum percentage was at 5% RPS in the concrete block. With the data obtained from the tests, it can be concluded that the use of RPS in concrete block can be a good by-product material to use in construction as it is eco-friendly and sustainable.